216k views
1 vote
In Exercise,Use properties of exponents to simplyfy the expression.
(e2)(e5)

User Dantes
by
5.0k points

1 Answer

5 votes

Answer:
(e^2)(e^5)=e^(7)

Explanation:

According to the product property of exponents :


a^m* a^n=a^(mn)

For example :
(5^9)(5^2)=5^(9+2)=5^(11)

Let's take one more example :


7^(-3)*7^4=7^(3+(-4))=7^(3-4)=7^(-1) [∵ (-)(+)=(-)]

The given expression :
(e^2)(e^5)

Using the product property of exponent , we get


(e^2)(e^5)=e^(2+5)=e^(7)

Hence, the required simplified expression would be
e^(7) .

User Liam Foley
by
4.8k points